Rapid and sensitive quantification of osimertinib in human plasma using a fully validated MALDI-IM-MS/MS assay - Fresnais, Margaux; Roth, André; Foerster, Kathrin; Jäger, Dirk; Pfister, Stefan; Haefeli, Walter E.; Burhenne, Jürgen; Longuespée, Rémi (Cancers, 2020)
The third-generation tyrosine kinase inhibitor (TKI), osimertinib, has revolutionized the treatment of patients with non-small cell lung carcinoma with epidermal growth factor receptor (EGFR)-activating mutation, and resistant to first- and second-generation TKIs. Osimertinib is now also proposed as a first-line therapy, thus extending the scope of applications in lung oncology. Personalized medicine approaches are still necessary to monitor if patients are exposed to adequate concentrations of osimertinib during their treatment. It would also help to understand the appearance of new resistances in patients after several months of dosing with osimertinib. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) is currently the gold standard for the quantification of drugs in plasma enabling pharmacokinetic analyses and patient monitoring. In the present study, we propose an alternative to LC-MS/MS methods for the rapid and sensitive quantification of osimertinib in plasma using matrix-assisted laser desorption/ionization (MALDI) -MS. The presented assay requires only 3 min per sample for their preparation, analysis, and data extraction, and less than 3 h for quantification. A lower limit of quantification (LLOQ) of 5 ng/mL in plasma was retrieved. The method was fully validated, following the guidelines of the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) for bioanalytical method validation. The present developments prove the importance to consider alternative MS assays for time-efficient quantification of small molecule inhibitors in plasma in the context of personalized medicine for targeted therapies.
Gesehen am 22.09.2020